2015
DOI: 10.1177/0394632015599705
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol-induced Sweet’s syndrome

Abstract: Sweet's syndrome, or acute febrile neutrophilic dermatosis, is an uncommon severe cutaneous condition, not previously associated with allopurinol therapy. We describe the case of an 87-year-old woman with hyperuricemia who developed classic Sweet's syndrome manifestations 8 days after being treated with allopurinol. Patient's symptoms included fever, painful edema in the hands and lower limbs with non-pruritic erythematous plaques topped by pus-filled skin blisters, right eye conjunctivitis, splenomegaly and j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…This difference is probably due to higher rate of parenteral antibiotics prescribed in Italy compared to the Northern European countries ( Davies et al, 2009 ). Moderate to severe skin/allergic reactions ( Polimeni et al, 2016 ) and application-site disorders represented the most common ADRs observed. These results might be partially explained by the higher rate of parenteral antibiotics among inpatients and the involvement of nurses and physicians in the project with a higher sensitiveness to identify ADRs.…”
Section: Discussionmentioning
confidence: 99%
“…This difference is probably due to higher rate of parenteral antibiotics prescribed in Italy compared to the Northern European countries ( Davies et al, 2009 ). Moderate to severe skin/allergic reactions ( Polimeni et al, 2016 ) and application-site disorders represented the most common ADRs observed. These results might be partially explained by the higher rate of parenteral antibiotics among inpatients and the involvement of nurses and physicians in the project with a higher sensitiveness to identify ADRs.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatologic complications of allopurinol can occur in up to 10%–15% of patients including a maculopapular eruption, pruritus, Sweet syndrome, and rarely, Stevens–Johnson syndrome/TEN 22 . Generally, the average duration from the administration of a causative agent to the onset of skin lesions is about 5–7 days in most cases 23–25 . Our patient presented 3 weeks after the initiation of allopurinol.…”
Section: Discussionmentioning
confidence: 72%
“…22 Generally, the average duration from the administration of a causative agent to the onset of skin lesions is about 5-7 days in most cases. [23][24][25] Our patient presented 3 weeks after the initiation of allopurinol. Given this time course, her skin eruption was initially presumed to be secondary to allopurinol.…”
Section: Discussionmentioning
confidence: 99%
“…Sweet’s syndrome, or acute febrile neutrophilic dermatosis, is an uncommon, severe cutaneous condition, characterized by the abrupt development of painful, tender, erythematous plaques, fever greater than 38°C, and a nodular perivascular neutrophilic dermal infiltrate without evidence of vasculitis on histologic examination [ 1 ][ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…SS is a potentially disabling disease, significantly associated with malignancies (15-20% of cases). Among these, hematologic neoplasms, particularly acute myeloid leukaemia (AML) and myelodysplastic syndromes are the most commonly reported [ 2 ][ 3 ].…”
Section: Introductionmentioning
confidence: 99%